2018
DOI: 10.1007/s00384-018-3153-0
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of robotic-assisted laparoscopic surgery for rectal cancer: results of a single high-volume center in Japan

Abstract: Our results suggest that RALS is technically feasible for rectal cancer and has good short- and long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 34 publications
2
21
2
2
Order By: Relevance
“…In Japan, Yamaguchi et al [65] and our group [66] recently reported favorable long-term survival rates with RRS for rectal cancer. Although these results were from single-center, single-arm, retrospective studies, the number of patients was adequate and the patients achieved better longevity at each stage compared with the national registry of patients with cancer of the rectum [67].…”
Section: Long-term Outcomesmentioning
confidence: 84%
“…In Japan, Yamaguchi et al [65] and our group [66] recently reported favorable long-term survival rates with RRS for rectal cancer. Although these results were from single-center, single-arm, retrospective studies, the number of patients was adequate and the patients achieved better longevity at each stage compared with the national registry of patients with cancer of the rectum [67].…”
Section: Long-term Outcomesmentioning
confidence: 84%
“…En cuanto a los resultados quirĂșrgicos encontrados en este estudio, el tiempo operatorio medio fue de 266 min, valor que se encuentra dentro del rango reportado en investigaciones previas, que oscila entre 180 a 360 min 10,24,33 . Se registra un mayor tiempo operatorio en la cirugĂ­a robĂłtica versus laparoscĂłpica 15 , con una diferencia media de 37,5 a 58 min que se atribuye al docking de la consola, el posicionamiento del instrumental y la curva de aprendizaje 15,33 . No obstante, como en la introducciĂłn de toda tĂ©cnica quirĂșrgica, se señala que con la mejora de la curva de aprendizaje se reduce el tiempo operatorio a largo plazo 24,27,34 .…”
Section: Resultsunclassified
“…Nuestro hallazgo concuerda con lo presentado en la literatura, en la que se describe una escasa pĂ©rdida sanguĂ­nea intraoperatoria, ademĂĄs, se señala que esta es igual o relativamente menor en comparaciĂłn a la cirugĂ­a laparoscĂłpica 2,9,11,15,17,19,[23][24][25][26]31,32 . Yamaguchi et al 33 , y Katsuno et al 10 Reintervenciones quirĂșrgicas* 5 13…”
Section: Resultsunclassified
“…Several current studies show that robotic rectal cancer surgery is feasible and safe in terms of surgical and oncologic results, particularly in technically difficult cases, such as narrow pelvises, distal tumors, and tumors that have been previously treated with radiotherapy and chemotherapy 12‐14 …”
Section: Discussionmentioning
confidence: 99%
“…A study of 551 patients operated by robotic surgery in a single‐center for the treatment of rectal cancer reported a median operating time of 257 min (109–683) and an estimated blood loss of 10 ml (0–823). Another single‐center study from 2015 reported a median operating time of 492 min and an estimated blood loss of 150 ml (20–500 ml) 13,19 …”
Section: Discussionmentioning
confidence: 99%